1, 5, 7‐Triazabicyclo[4.4.0]dec‐5‐ene Enhances Activity of Peroxide Intermediates in Phosphine‐Free α‐Hydroxylation of Ketones. Issue 12 (3rd February 2021) - Wang, Yongtao; Lu, Rui; Yao, Jia; Li, Haoran
Abstract: The critical role of double hydrogen bonds was addressed for the aerobic α‐hydroxylation of ketones catalyzed by 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD), in the absence of either a metal catalyst or phosphine reductant. Experimental and theoretical investigations were performed to study the mechanism. In addition to initiating the reaction by proton abstraction, a more important role of TBD was revealed, that is, to enhance the oxidizing ability of peroxide intermediates, allowing DMSO to be used rather than commonly used phosphine reductants. Further characterizations with nuclear Overhauser effect spectroscopy (NOESY) confirmed the presence of double hydrogen bonds between TBD and the ketone, and kinetic studies suggested the attack of dioxygen on the TBD‐enol adduct to be the rate‐determining step. This work should encourage the application of TBD as a catalyst for oxidations. Abstract : The dual catalytic role of 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) was revealed for the aerobic α‐hydroxylation of ketones under a metal‐ and phosphine‐free method. By means of a double‐proton‐transfer process, TBD activates the α‐C(sp 3 )−H bond of ketones, avoiding the necessity of an alkali metal. Most importantly, TBD enhances the activity of the peroxide intermediate through the double hydrogen bonds, allowing reduction by DMSO in the absence of a phosphine reductant.